Tapestry of Mental Illnesses: Exploring Causes, Symptoms and Mechanisms Behind the Veil of Depression - Karuna Gautam; Poonam Singh (Contemporary Research and Perspectives in Biological Science Vol. 5, 2024)
Depression, a pervasive mental illness globally, manifests as a state of despair leading to diminished motivation and interest in life’s rewards. This chapter examines various risk factors contributing to depression, encompassing genetic, chemical, psychological, environmental, and biological elements. It delves into the multifaceted nature of depression, exploring its diverse endophenotypes such as anhedonia, anxiety, despair, and hopelessness. By synthesizing current understandings of depression’s etiology, such as alterations in neurogenesis and neuroplasticity, the chapter underscores the need for future research to explore these biological mechanisms, particularly their implications for developing targeted interventions. The chapter also discusses the detrimental impact of depression on brain regions like the amygdala, hippocampus, and pre-frontal cortices, as well as its effects on gastrointestinal, immune, and endocrine systems. Moreover, the possible treatment approaches for depression in the current scenario and its societal impacts are also included for a better understanding of depression as a common mental disorder. Additionally, the discussion on the impact of depression on critical brain regions and body systems emphasizes the necessity for integrated treatment approaches that consider both psychological and physiological aspects. This holistic perspective can inform clinical practices by advocating for personalized treatment plans that incorporate evidence-based therapies like cognitive behavioral therapy (CBT) and mindfulness-based approaches, thus enhancing the effectiveness of interventions for individuals suffering from depression. Overall, the chapter contributes significantly to the field by not only elucidating the complexities of depression but also suggesting pathways for future exploration and improved clinical outcomes.